Rinorea gemmulata (Violaceae): A New Species from Eastern Brazil - Oliveira, José Florencio Cerqueira; de Queiroz, Luciano Paganucci (Phytotaxa, 2020)
We describe and illustrate here a new species of Rinorea from the Brazilian states of Bahia and Espírito Santo, under the name Rinorea gemmulata. The new species occurs in the understory of seasonally dry riparian and semi-deciduous forests. The new species could be diagnosed by the combination of opposite leaves, free stamens, velutinous connective and for the unique presence of perulate buds. We provide a distribution map, a preliminary IUCN conservation assessment, and illustrations, as well as morphological comparison with the sympatric R. ramiziana and the putatively related R. vaupesana and R. villosiflora.